2005
DOI: 10.4049/jimmunol.174.3.1317
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a B220+ Lymphoid Cell Subpopulation with Immune Modulatory Functions in Nasal-Associated Lymphoid Tissues

Abstract: Complex mechanisms operate on mucosal tissues to regulate immune responsiveness and tolerance. When the lymphocyte subpopulations from murine nasal-associated lymphoid tissues (NALT) were characterized, we observed an accumulation of B220lowCD3lowCD4−CD8−CD19−c-Kit+ cells. TCR transgenic mice and athymic mice were used for monitoring T cell lineage and the presence of extrathymic T cell precursors. The majority of cells from NALT exhibited a T cell precursor phenotype (CD4−CD8−CD19−c-Kit+). Fas-independent apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 52 publications
2
14
1
Order By: Relevance
“…These include several subsets of recently characterized innate lymphoid cells, 43 the multipotent progenitor type 2 cells, 44 and the B220 low CD19 2 regulatory cell population identified in the nasal associated lymphoid tissue. 45 These require further examination in the context of c-kit-related mast cell deficiency models. OT-II Treg cells are enhanced in the Kit W-sh/W-sh MLNs after oral tolerance induction to OVA through a mast cell-independent mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…These include several subsets of recently characterized innate lymphoid cells, 43 the multipotent progenitor type 2 cells, 44 and the B220 low CD19 2 regulatory cell population identified in the nasal associated lymphoid tissue. 45 These require further examination in the context of c-kit-related mast cell deficiency models. OT-II Treg cells are enhanced in the Kit W-sh/W-sh MLNs after oral tolerance induction to OVA through a mast cell-independent mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have suggested that some DN T cells may develop in the bone marrow (51)(52)(53), appendix (32), female genital tract (20), NALT (33) and liver (34,35). In addition, the levels of DN T cells in the female genital tract or the NALT of nude mice was found to be similar to that found in wild-type mice, indicating that development of DN T cells within these tissues does not require the thymus (20,33,51). Strober's group (54) has also shown that precursors to functional CD4 ϩ and CD8 ϩ T cells are found in the bone marrow, not the thymus, and that functional T cells could develop from these precursors in athymic nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, DN T cell numbers may also increase due to direct activation and expansion of a pre-existing population of DN T cells. Furthermore, studies have also suggested that some DN T cell populations may develop extrathymically in the appendix (32), female genital tract (20), nasal-associated lymphoid tissue (NALT) (33), or the liver (34,35). Given the significant roles that DN Tregs play in various disease models, further characterization of their developmental pathways may facilitate expansion or reduction of DN Tregs and therefore better control of pathological immune responses.…”
Section: R Egulatory T Cells (Tregs)mentioning
confidence: 99%
“…Interestingly, this reduction in lymphocyte infiltration was associated with a decrease in CD3 low B220 + cells, which are derived from thymus. Recent studies suggest that the CD3 low B220 + cells in lpr mice are innate lymphoid cells and play important roles in organ inflammation (31). It will be interesting to further study how Hrd1 regulates the development of CD3 low B220 + cells independent of Fas destruction.…”
Section: Discussionmentioning
confidence: 99%